Design and Performance Test of Corn Seeder Integrated with Fertilizer Applicator - Muhammad Asshidiq Ansar; Ansar Ansar; Gagassage Nanaluih De Side; Gagassage Nanaluih De Side (The University of Lampung, 2025)
Along with the increasing demand for corn in the country, the use of agricultural tools and machines to increase corn productivity is very important. Therefore, this study aims to design and test the performance of a corn seeder integrated with fertilizer applicator. This tool is designed using the principles of agricultural mechanics. The research stages began with conducting a feasibility study, designing a prototype of the tool, then conducting performance testing on agricultural land. The results showed that the majority of farmers considered this tool very effective and efficient to use compared to a digging tool. The results of the performance test on farmers' land also showed that this tool was able to plant corn seeds with uniform depth and spacing and distribute fertilizer evenly. All components of the corn seeder function properly, so it is suitable for use to increase the productivity of corn farmers' land. This corn seeder has met the category requirements as a corn seeder and fertilizer applicator with a manual operating system. The application of this corn seeder has the potential to increase land productivity and can facilitate the process of planting corn seeds. Keywords: Corn seeders, Corn, Land productivity, Planting holes, Respondents.